Analysis of the influence of organizational culture, leadership style, and job satisfaction on employee performance at PT Kalfaz Sadhara - Nur Rahman; M. Chaerul Rizky; M. Alfahmi (Junal Ilmu Manajemen, 2023)
This study aims to determine and analyze the extent to which organizational culture, leadership style, and job satisfaction influence the performance of PT Kalfaz Sadhara's employees. This study uses a quantitative method with the type of data collected is primary data which is processed using SPSS. The population in this study was 65. Data was collected by conducting interviews and distributing questionnaires to respondents. The data analysis technique used is multiple linear analysis. The results of the study suggest that partially organizational culture, leadership style, and job satisfaction have a positive effect on the performance of employees of PT Kalfaz Sadhara. And simultaneously shows that organizational culture, leadership style, and job satisfaction simultaneously has a positive effect on the performance of employees of PT Kalfaz Sadhara. The influence contribution given by all variables is 48.4%.